2014
DOI: 10.1080/15512169.2013.862502
|View full text |Cite
|
Sign up to set email alerts
|

To Resist, Acquiesce, or Internalize: Departmental Responsiveness to Demands for Outcomes Assessment

Abstract: Over the last 30 years, higher education has received the assessment movement with a substantial amount of skepticism. The purpose of this study is to advance our understanding of political science's responsiveness to assessment reform pressures using neoinstitutional theory. The influence of public status, institutional type, and accreditation region on curricular planning and assessment responsiveness is tested. Using an index to measure the responsiveness of a stratified, random sample of program descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…At the program level, professional studies and accredited programs have embraced assessment (Ewell, Paulson, and Kinzie 2011). Conversely, the humanities and social sciences are more likely to “decouple” assessment from their daily work (Young, Cartwright, and Rudy 2014).…”
Section: Explaining Student Outcomes Assessment Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…At the program level, professional studies and accredited programs have embraced assessment (Ewell, Paulson, and Kinzie 2011). Conversely, the humanities and social sciences are more likely to “decouple” assessment from their daily work (Young, Cartwright, and Rudy 2014).…”
Section: Explaining Student Outcomes Assessment Implementationmentioning
confidence: 99%
“…Skepticism about the purposes and value of assessment pervades academia, especially the arts and sciences (Ewell, Paulson, and Kinzie 2011). In political science—which has accomplished as much as any non-accredited discipline to promote understanding and best practices of assessment (Deardorff, Hamann, and Ishiyama 2009)—the dominant stance of most programs is acquiescence to outside demands rather than commitment from faculty to improve curriculum and instruction (Young, Cartwright, and Rudy 2014).…”
mentioning
confidence: 99%
“…As to which curricular goals political scientists value most, the outcomes model in the USA devolves the responsibility to departments to decide what is appropriate for their programs. With some degree of variation across regional accrediting agencies, institutions are permitted to define the learning goals appropriate to their missions (Young, Cartwright and Rudy 2014). Within constraints set by the accrediting body and individual colleges or universities, academic departments have autonomy to define program and course outcomes.…”
Section: The Outcomes-based Model Devolution and Standardizationmentioning
confidence: 99%
“…Looking at learning outcomes in political science departmental websites, we can get a sense of the diversity of the discipline around the issue of curriculum goals. Only tentative generalizations can be made, since only around one-quarter of a random sample of departments, including those in doctoral-granting institutions, provided clear learning outcomes on the Web (Young, Cartwright and Rudy 2014). Focusing on a sample of baccalaureate degree-only programs in political science, McClellan and Maurer (2014) found that 37 percent listed outcomes.…”
Section: The Outcomes-based Model Devolution and Standardizationmentioning
confidence: 99%
See 1 more Smart Citation